2005
DOI: 10.1063/1.1852717
|View full text |Cite
|
Sign up to set email alerts
|

Giant barrier layer capacitance effects in the lithium ion conducting material La0.67Li0.25Ti0.75Al0.25O3

Abstract: Articles you may be interested inThe sintering temperature effects on the electrical and dielectric properties of Li 0.05 Ti 0.02 Ni 0.93 O ceramics prepared by a direct thermal decomposition method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…25 Ti 0.75 Al 0.25 O 3 . [10] The chemical and physical properties of materials are intimately related to their crystal structure and microstructure. Therefore, the knowledge of the crystal structure of these oxides, in particular the location of the Li ions, is essential to understand their physicochemical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…25 Ti 0.75 Al 0.25 O 3 . [10] The chemical and physical properties of materials are intimately related to their crystal structure and microstructure. Therefore, the knowledge of the crystal structure of these oxides, in particular the location of the Li ions, is essential to understand their physicochemical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these materials are cubic and hexagonal perovskite oxide ceramics, including CaCu 3 Ti 4 O 12 (CCTO) [1][2][3][4][5][6][7][8], ACu 3 Ti 4 O 12 (A = La 2/3 , Bi 2/ 3 , Na 1/2 Bi 1/2 , etc.) [9][10][11], Ta-doped BaTi 0.85 Zr 0.15 O 3 [12], La 0.67 Li x Ti 1-x Al x O 3 (x = 0.2, 0.25) [13,14], Fe-based complex perovskites B(Fe 1/2 M 1/2 )O 3 (B = Ba, Sr, and Ca, M = Nb, Ta, and Sb) [15][16][17], and Ba 4 YMn 3 O 11.5 [18], with the exception of a non-perovskite Li and Ti doped NiO ceramics [19]. It could be observed that most materials with giant dielectric constant share common features, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] A different explanation to the peculiar dielectric behavior of this material has been given by Sinclair and co-workers. 15 We have reported the dielectric behavior of the 16 This material has a perovskite-related structure and is a lithium ion conductor; in fact, it is the oxide with the highest ionic conductivity of the La 2/3 Li 3x Ti 1−x Al x O 3 family. The conducting phase has been related to the formation of Ti 3+ .…”
Section: Introductionmentioning
confidence: 99%